Gelatin / PVA-based double-network structure hydrogel, flexible hydrogel electrode, hydrogel-TENG sensor and preparation method

By inventing glue/polyvinyl alcohol-based dual network structure hydrogels, flexible hydrogel electrodes and hydrogel-trigel electrical sensors were prepared, which solved the problems of external power dependence, complex equipment coordination and insufficient material stability in existing electronic skin technology, achieved self-powered and non-contact sensing, and improved the application prospects and reliability of electronic skin.

CN119899401APending Publication Date: 2025-04-29HEBEI UNIV OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510063249.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing electronic skin technology has problems such as external power dependence, complex equipment coordination, rigid structure affects aesthetics and safety, high preparation cost, insufficient material stability and durability, which limits its large-scale application and reliability.

Method used

Develop a gelatin/polyvinyl alcohol-based dual network structure hydrogel. By preparing flexible hydrogel electrodes and hydrogel-trigel electrical sensors, self-powered and non-contact sensing are achieved, combining functional components such as glycerol, sodium chloride, citric acid and sodium citrate to improve the mechanical properties, adhesion and biocompatibility of the hydrogel.

Benefits of technology

It has achieved thin, soft, high transparency, high stability and good biocompatibility electronic skin, expanding its application prospects, including electrocardiogram monitoring and intelligent health monitoring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899401A_ABST
    Figure CN119899401A_ABST
Patent Text Reader

Abstract

The invention discloses gelatin / PVA (Polyvinyl Alcohol)-based double-network structure hydrogel, a flexible hydrogel electrode, a hydrogel-TENG sensor and a preparation method. The gelatin / polyvinyl alcohol-based double-network structure hydrogel with high flexibility, transparency, adhesion, self-healing capability, degradability and biocompatibility is prepared by introducing functional components including glycerol, sodium chloride, citric acid and sodium citrate into gelatin and polyvinyl alcohol. According to the application, poly (3, 4-ethylenedioxythiophene)-polystyrene sulfonate, graphene and cobalt nano-porous carbon are respectively added into gelatin / polyvinyl alcohol-based hydrogel with a double-network structure, so that a flexible hydrogel electrode and a hydrogel-triboelectric sensor charge sensitive layer are respectively obtained; and the hydrogel-based flexible non-contact triboelectric sensor with biological friendliness is finally prepared by combining the hydrogel-based flexible non-contact triboelectric sensor with biological friendliness. The hydrogel-triboelectric sensor is expected to play a greater role in the fields of intelligent medical treatment, flexible electronic equipment, human-computer interaction and the like in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogels, and in particular to a gelatin / polyvinyl alcohol (PVA)-based double-network structure hydrogel, a flexible hydrogel electrode, a hydrogel-triboelectric (TENG) sensor and a preparation method thereof. Background Art

[0002] Electronic skin is a flexible electronic sensor system designed to mimic the structure and function of human skin. With the advancement of flexible electronics, nanotechnology and material science, microelectronic devices such as sensors, electronic components and transistors have become flexible and wearable. Electronic skin has shown broad application prospects in the fields of smart medical care, human-computer interaction, virtual reality and artificial intelligence.

[0003] At present, electronic skin technology has made significant progress, with major breakthroughs in materials, preparation processes, sensor design and integrated systems. Its sensing function is becoming more and more perfect, and it can monitor and sense various external environmental parameters such as temperature, humidity, pressure, stretching and light in real time. At the same time, electronic skin has the characteristics of fast response and high sensitivity, and can interact and communicate with the human body and robots in real time.

[0004] However, there are still some key problems with existing electronic skin technology. Most electronic skins require external power supply and coordination between multiple devices. Except for the sensing part, most components are rigid structures, which not only affects the aesthetics, comfort and safety, but also is not conducive to signal acquisition. In addition, factors such as high preparation cost, complex manufacturing process and small production scale limit the large-scale application and promotion of electronic skin. The material stability and durability of some flexible electronic skins need to be improved, and they are prone to degradation and damage after long-term use, affecting their reliability and service life. The sensing function and integrated system of electronic skin still have certain limitations, and further improvement and optimization are needed to meet the needs of different application scenarios. For electronic skin in contact with human skin, its biocompatibility and safety are particularly critical, and relevant research and evaluation need to be strengthened to ensure that it is harmless to human health. Therefore, it is urgent to develop and construct an integrated self-powered electronic skin that is thin, soft, highly transparent, highly stable and has good biocompatibility to promote the development and widespread application of electronic skin technology. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a gelatin / polyvinyl alcohol-based double network structure hydrogel, a flexible hydrogel electrode, a hydrogel-triboelectric sensor and a preparation method.

[0006] In a first aspect, the present invention provides a method for preparing a gelatin / polyvinyl alcohol-based double network structure hydrogel, which is achieved through the following technical scheme.

[0007] A method for preparing a gelatin / polyvinyl alcohol-based double network structure hydrogel comprises the following steps:

[0008] A1. Dissolve sodium chloride, citric acid and sodium citrate in deionized water, then add glycerin, gelatin powder and polyvinyl alcohol powder, and soak for 2 to 3 hours; wherein the mass ratio of sodium chloride, citric acid, sodium citrate, deionized water, glycerin, gelatin and polyvinyl alcohol is 9.0-9.5:0.8-1.2:8-12:75-85:55-65:35-45:35-45;

[0009] A2. The mixture obtained in step A1 is heated for 1 to 1.5 hours until completely dissolved, and the temperature is controlled in the range of 90 to 95°C;

[0010] A3. The solution obtained in step A2 is stirred at a speed of 1000 to 1500 revolutions per minute for 2 to 2.5 hours until it is uniform to obtain a hydrogel solution;

[0011] A4. Pour the hydrogel solution obtained in step A3 evenly onto a coating machine, apply it to a film of a certain thickness, and let it stand to cool and form to obtain a gelatin / polyvinyl alcohol-based double network structure hydrogel.

[0012] In a second aspect, the present invention provides a gelatin / polyvinyl alcohol-based double network structure hydrogel, which is achieved through the following technical solution.

[0013] A gelatin / polyvinyl alcohol-based double network structure hydrogel prepared by the above preparation method.

[0014] In a third aspect, the present invention provides a use of a gelatin / polyvinyl alcohol-based double network structure hydrogel, which is achieved through the following technical solution.

[0015] An application of the gelatin / polyvinyl alcohol-based double network structure hydrogel in the preparation of a flexible hydrogel electrode or a hydrogel-triboelectric sensor charge sensitive layer or a hydrogel-triboelectric sensor.

[0016] In a fourth aspect, the present invention provides a method for preparing a flexible hydrogel electrode, which is achieved through the following technical solution.

[0017] A method for preparing a flexible hydrogel electrode comprises the following steps:

[0018] B1. Dissolve sodium chloride, citric acid and sodium citrate in deionized water, add polyethylene dioxythiophene-polystyrene sulfonate dispersion and graphene dispersion and stir evenly, then add glycerol, gelatin powder and polyvinyl alcohol powder and soak for 2 to 3 hours; wherein the mass ratio of sodium chloride, citric acid, sodium citrate, deionized water, glycerol, gelatin, polyvinyl alcohol, polyethylene dioxythiophene-polystyrene sulfonate dispersion and graphene dispersion is 9.0-9.5:0.8-1.2:8-12:75-85:55-65:35-45:35-45:75-85:155-165;

[0019] B2. The mixture obtained in step B1 is heated for 1 to 1.5 hours until completely dissolved, and the temperature is controlled in the range of 90 to 95°C;

[0020] B3. The solution obtained in step B2 is stirred at a speed of 1000 to 1500 revolutions per minute for 2 to 2.5 hours until it is uniform to obtain a hydrogel solution;

[0021] B4. Pour the hydrogel solution obtained in step B3 evenly on a coating machine, scrape and coat it to obtain a film of a certain thickness, let it stand and cool to form a flexible hydrogel electrode.

[0022] In a fifth aspect, the present invention provides a flexible hydrogel electrode, which is realized by the following technical solution.

[0023] A flexible hydrogel electrode prepared by the above preparation method.

[0024] In a sixth aspect, the present invention provides a use of a flexible hydrogel electrode, which is achieved through the following technical solution.

[0025] An application of the above-mentioned flexible hydrogel electrode in the preparation of a hydrogel-triboelectric sensor.

[0026] In a seventh aspect, the present invention provides a method for preparing a charge sensitive layer of a hydrogel-triboelectric sensor, which is achieved through the following technical solution.

[0027] A method for preparing a hydrogel-triboelectric sensor charge sensitive layer comprises the following steps:

[0028] C1. Dissolve sodium chloride, citric acid and sodium citrate in deionized water, then add cobalt nanoporous carbon, glycerol, gelatin powder and polyvinyl alcohol powder, and soak for 2 to 3 hours; wherein the mass ratio of sodium chloride, citric acid, sodium citrate, cobalt nanoporous carbon, deionized water, glycerol, gelatin and polyvinyl alcohol is 9.0-9.5:0.8-1.2:8-12:5-10:75-85:55-65:35-45:35-45;

[0029] C2. The mixture obtained in step C1 is heated for 1 to 1.5 hours until completely dissolved, and the temperature is controlled in the range of 90 to 95°C;

[0030] C3. The solution obtained in step C2 is stirred at a speed of 1000 to 1500 revolutions per minute for 2 to 2.5 hours until it is uniform to obtain a hydrogel solution;

[0031] C4. Pour the hydrogel solution obtained in step C3 evenly on a coating machine, scrape and coat it to obtain a film of a certain thickness, let it stand and cool to form a hydrogel-triboelectric sensor charge sensitive layer.

[0032] In an eighth aspect, the present invention provides a hydrogel-triboelectric sensor charge sensitive layer, which is realized by the following technical solution.

[0033] A hydrogel-triboelectric sensor charge sensitive layer prepared by the above preparation method.

[0034] In a ninth aspect, the present invention provides a use of a hydrogel-triboelectric sensor charge sensitive layer, which is achieved through the following technical solution.

[0035] An application of the above hydrogel-triboelectric sensor charge sensitive layer in the preparation of a hydrogel-triboelectric sensor.

[0036] In a tenth aspect, the present invention provides a method for preparing a hydrogel-triboelectric sensor, which is achieved through the following technical solution.

[0037] A method for preparing a hydrogel-triboelectric sensor comprises the following steps:

[0038] D1. cutting the above-prepared flexible hydrogel electrode and the above-prepared hydrogel-triboelectric sensor charge sensitive layer;

[0039] D2. Lead out a silver wire from the flexible hydrogel electrode;

[0040] D3. Bond the flexible hydrogel electrode, silver wire and the charge sensitive layer of the hydrogel-triboelectric sensor to obtain the hydrogel-triboelectric sensor.

[0041] In the eleventh aspect, the present invention provides a hydrogel-triboelectric sensor, which is realized by the following technical solution.

[0042] A hydrogel-triboelectric sensor prepared by the above method.

[0043] This application has the following beneficial effects.

[0044] The gelatin / polyvinyl alcohol-based double network structure hydrogel prepared by the present invention has high flexibility, transparency, adhesion, self-healing ability, degradability and biocompatibility, and can be expanded to make hydrogel-type flexible electrodes for electrocardiogram monitoring and self-powered hydrogel-type triboelectric sensors to achieve non-contact sensing, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a schematic diagram of the double network structure hydrogel of gelatin / polyvinyl alcohol prepared by the present invention;

[0046] Figure 2 It is a rheological characterization diagram of the biogels of different formulations of the present invention in the temperature range of 10 to 50°C;

[0047] Figure 3 is a physical picture of the hydrogel material of the present invention adhered to different surfaces (copper foil, paper, acrylonitrile-butadiene-styrene copolymer plastic, glass, ethylene-vinyl acetate copolymer, aluminum and polystyrene plastic culture dish);

[0048] Figure 4 These are photos of hydrogels of different shapes according to the present invention.

[0049] Figure 5 It is a microscopic photograph of the skin surface thinly coated with the hydrogel of the present invention and a comparative picture of the wound patch peeled off after being adhered to the skin surface for 7 days;

[0050] Figure 6 This is a photograph of the shape monitoring of the hydrogel film of the present invention within 14 days;

[0051] Figure 7 This is a curve chart of monitoring water loss of the hydrogel film of the present invention within 14 days;

[0052] Figure 8 is a schematic diagram of the lap shear test of the hydrogel of the present invention, the adhesion strength to different materials, and the repeated adhesion strength to polyimide film, copper foil and pig skin;

[0053] Fig. 9 The displacement-peel strength curves of the hydrogel of the present invention and skin in different states (hair, sweat, smooth); the displacement-tensile strength curves of the hydrogels of different thicknesses (0.3, 0.4, 0.5, 0.6, 0.7 mm) in the tensile fracture state; the tensile strength-strain curve of the hydrogel with a thickness of 0.4 mm after 1000 cycles;

[0054] Fig.10 The gel electrode of the present invention is applied to an electrocardiogram test chart;

[0055] Fig.11 The waveform diagram of the electrocardiogram signal monitored by the hydrogel electrode of the present invention within 6 seconds after exercise and at rest;

[0056] Fig.12 These are the ECG monitoring waveforms of the hydrogel electrode of the present invention in the "standing" and "walking" states at the 0th, 7th and 14th days respectively;

[0057] Fig.13 It is a comparison diagram of the ECG signal waveforms and signal-to-noise ratios recorded and monitored by the hydrogel electrode of the present invention and the commercial electrode in different states (bending, squeezing, stretching);

[0058] Fig.14 The photos are of the damaged thin film electrode of the present invention being heated and healed, and the photos of the load-bearing capacity after being stretched and healed;

[0059] Fig.15 It is a waveform diagram of the ECG monitoring signal of the thin film electrode in the intact, damaged and healed states of the present invention;

[0060] Fig.16 Schematic diagram of the hydrogel-triboelectric sensor and sensor principle of the present invention;

[0061] Fig.17 This is a graph showing the effects of the cobalt nanoporous carbon content and different cathode materials on sensor performance of the present invention;

[0062] Fig.18 This is a performance characterization diagram of the hydrogel-triboelectric sensor of the present invention;

[0063] Fig.19 The present invention uses rubber gloves as the positive electrode material, and the finger completes the "approach-contact-release-distance" action cycle in front of the hydrogel / triboelectric sensor, and the distance-time and relative voltage-time relationship curve between the finger and the hydrogel-triboelectric sensor;

[0064] Fig. 20 The sensor output signal curves when the experimenter of the present invention completes the arm swinging action at a distance of 0.8, 1.6, 2.4, 3.2, and 4.0 meters from the hydrogel-triboelectric sensor, and the sensor output signal curves when the experimenter completes the arm swinging, jumping jacks, jogging in place, and high-five actions at a distance of 0.8 meters from the hydrogel-triboelectric sensor, respectively;

[0065] Fig.21 It is a graph of output waveforms of the 3×3 hydrogel-triboelectric sensor array of the present invention respectively identifying the “L, Z, S” tracks. DETAILED DESCRIPTION

[0066] Gelatin is a common natural polymer, mainly extracted from connective tissues such as animal skin and bones, with good gelation, degradability and biocompatibility. However, the mechanical properties of gelatin-based hydrogels are poor, which limits their wide application. Polyvinyl alcohol is a high molecular polymer formed by the polymerization of vinyl alcohol monomers. Due to its good biocompatibility, it is widely used in the fields of medicine and bioengineering. Polyvinyl alcohol hydrogels have high strength and toughness, and perform well in load bearing and stress distribution.

[0067] In order to further improve the comprehensive performance of the hydrogel, this application designs a double-network hydrogel based on gelatin and polyvinyl alcohol, and introduces functional ingredients such as glycerol, sodium chloride, citric acid and sodium citrate. Thanks to the addition of polyvinyl alcohol, the double-network hydrogel maintains the flexibility of gelatin while improving the strength, thereby improving the overall mechanical properties. The addition of functional ingredients not only enhances the mechanical properties of the hydrogel, but also improves its adhesion and water retention capacity. The hydroxyl group (-OH) in the polyvinyl alcohol molecule and the hydroxyl group (-OH), carboxyl group (-COOH) and amino group (-NH 2 ) can form hydrogen bonds with hydrogen atoms in other substances, enhancing the adhesion of hydrogels. In addition, cross-linking may occur between polyvinyl alcohol and gelatin molecules to form a network structure, which improves the adhesion of hydrogels to other substances through bridging.

[0068] The experimental results show that the adhesion strength of gelatin and polyvinyl alcohol-based hydrogels on a variety of materials are: polyvinyl chloride (9.620 kPa), copper sheet (111.593 kPa), ethyl cellulose film (123.605 kPa), polyimide film (174.631 kPa), paper (117.895 kPa), pig skin (24.524 kPa) and polydimethylsiloxane (9.529 kPa). In addition, the hydrophilic groups in gelatin and the water absorption of polyvinyl alcohol give the hydrogel a long-term anti-drying ability. The addition of glycerol further enhances the water retention effect of the hydrogel by forming stable hydrogen bonds.

[0069] Gelatin has special thermal phase transition properties. As the temperature changes, the random coils and triple helical non-covalent crosslinks in the gelatin molecules will depolymerize and aggregate. By introducing functional ingredients such as glycerol, sodium chloride, citric acid and sodium citrate, and adjusting the molecular weight and crosslinking density in the gel, the solid-liquid phase transition temperature of the hydrogel can be changed, making it suitable for human epidermal applications. The adjusted solid-liquid phase transition temperature of the hydrogel reaches 38.15°C, which can meet the general adhesion conditions of the human epidermis.

[0070] Flexible electrodes are electronic technologies that make electronic devices on flexible or ductile plastic or thin metal substrates. Traditional rigid electrodes are at risk of damaging tissues in medical applications, such as measuring central nervous system currents, cardiac currents, etc. Therefore, flexible electronic devices have emerged and have important application significance. Graphene has excellent electrical conductivity, thermal conductivity and surface area, and is one of the ideal materials for preparing high-performance electrodes. Polyethylene dioxythiophene-polystyrene sulfonate dispersion composites also have excellent conductivity, transparency and flexibility. Combining graphene and polyethylene dioxythiophene-polystyrene sulfonate dispersion with gelatin / polyvinyl alcohol double network structure hydrogel can realize the extended application of hydrogel-flexible electrodes.

[0071] In recent years, miniaturized, highly integrated flexible wearable smart devices have attracted much attention. Non-contact friction nanogenerator (triboelectric) sensors with high sensitivity, fast response speed and self-powered energy use the mechanical energy generated by friction to drive the movement of charges between nanomaterials, realize self-powered and non-contact energy conversion and data acquisition, and have broad application prospects in environmental monitoring and intelligent health monitoring. Cobalt nanoporous carbon is a nitrogen-doped carbide based on a metal organic framework. Its high specific surface area and rich pore structure are conducive to the adsorption of molecules and catalytic reactions, and improve the electronegativity. The cobalt nanoporous carbon particles are uniformly mixed into the gelatin / polyvinyl alcohol double network structure hydrogel to obtain a hydrogel with strong electrostatic induction ability. By making it into a thin film and combining it with the aforementioned thin film electrode, the expanded application of the hydrogel can be realized-a hydrogel-based flexible non-contact triboelectric sensor that is both biofriendly.

[0072] The invention will be further described below with reference to the accompanying drawings and embodiments.

[0073] The polyethylene dioxythiophene-polystyrene sulfonate used in the following examples of this application was purchased from Zhuhai Kaiwei New Material Technology Co., Ltd.;

[0074] The cobalt nanoporous carbon used in the following examples of the present application is a homemade material, and the preparation raw materials include 2-methylimidazole purchased from Dalian Meilun Biotechnology Co., Ltd., cobalt nitrate hexahydrate purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and methanol purchased from Aladdin Reagent (Shanghai) Co., Ltd.

[0075] The preparation process of cobalt nanoporous carbon is as follows:

[0076] First, prepare the corresponding precursor: (1) dissolve 3.3 g of cobalt nitrate hexahydrate in 45 ml of methanol, and dissolve 3.7 g of 2-methylimidazole in 90 ml of methanol. Mix the two solutions and stir at room temperature at 450 rpm for 2 hours, then let the solution stand for 24 hours for aging and stratification;

[0077] (2) Discard the upper part of the solution and keep the lower part containing the dark precipitate. Then centrifuge the solution at 6000 rpm for 5 minutes, then discard the upper part and collect the purple precipitate. Wash the precipitate repeatedly with ethanol through centrifugation until the washing solution is transparent. Pour the final washing solution into a funnel and filter it with ethanol.

[0078] Subsequently, the precursor was carbonized: (1) purple ZiF-67 powder was obtained after standing at 60 °C for 24 h under vacuum. The powder was then ground into a fine powder using a mortar and pestle;

[0079] (2) ZiF-67 powder was carbonized at 800° C. in a nitrogen flow at a heating rate of 5° C. per minute until reaching 800° C., and the powder was annealed for 5 hours to obtain cobalt nanoporous carbon powder.

[0080] Example 1: Preparation of gelatin / polyvinyl alcohol-based double network structure hydrogel solution

[0081] (1) Dissolve 0.46 g of sodium chloride, 0.05 g of citric acid, and 0.5 g of sodium citrate in 4 ml of deionized water;

[0082] (2) Add 3 g glycerol, 2 g gelatin powder, and 0.7 g polyvinyl alcohol powder and soak for 2 hours;

[0083] (3) heating the mixture for 1 hour until it is completely dissolved, with the temperature controlled at 90°C;

[0084] (4) The obtained solution was stirred at a speed of 1000 revolutions per minute for 2 hours until it was in a uniform state, thereby obtaining a hydrogel solution.

[0085] Example 2: Preparation of gelatin / polyvinyl alcohol-based double network structure hydrogel film

[0086] (1) Pour the uniform hydrogel solution obtained above evenly onto a coating machine and apply by knife coating to obtain a 400 μm thin film;

[0087] (2) Allow the film to cool and then cut into appropriate sizes.

[0088] Example 3: Preparation of flexible hydrogel electrode solution

[0089] (1) Dissolve 0.46 g of sodium chloride, 0.05 g of citric acid, and 0.5 g of sodium citrate in 4 ml of deionized water;

[0090] (2) adding 1 ml of polyethylene dioxythiophene-polystyrene sulfonate dispersion and 1 ml of graphene dispersion, and stirring at 1000 rpm for 2 hours until the mixture is homogeneous;

[0091] (3) Add 3 g glycerol, 2 g gelatin powder, and 0.7 g polyvinyl alcohol powder and soak for 2 hours;

[0092] (4) heating the resulting mixture for 1 hour until it is completely dissolved, with the temperature controlled at 90° C.;

[0093] (5) The solution was placed in a magnetic stirrer and stirred at 1000 revolutions per minute for 2 hours to obtain a uniform hydrogel solution.

[0094] Example 4: Preparation of flexible hydrogel electrodes

[0095] (1) Pour the uniform hydrogel solution obtained above evenly onto a coating machine and apply by knife coating to obtain a 400 μm thin film;

[0096] (2) Allow the film to cool and then cut into appropriate sizes.

[0097] Example 5: Preparation of hydrogel-triboelectric sensor charge sensitive layer solution

[0098] (1) 0.46 g of sodium chloride, 0.05 g of citric acid, and 0.5 g of sodium citrate were dissolved in 4 ml of deionized water;

[0099] (2) Add 0.3 g of cobalt nanoporous carbon, 3 g of glycerol, 2 g of gelatin powder, and 0.7 g of polyvinyl alcohol powder and soak for 2 hours;

[0100] (3) heating the resulting mixture for 1 hour until it is completely dissolved, with the temperature controlled at 90° C.;

[0101] (4) The solution was placed in a magnetic stirrer and stirred at 1000 revolutions per minute for 2 hours to obtain a uniform hydrogel solution.

[0102] Example 6: Preparation of hydrogel-triboelectric sensor charge sensitive layer

[0103] (1) Pour the uniform hydrogel solution obtained above evenly onto a coating machine and apply by knife coating to obtain a 400 μm thin film;

[0104] (2) Allow the film to cool and then cut into appropriate sizes.

[0105] Example 7: Preparation of hydrogel-triboelectric sensor

[0106] (1) Cut the electrode layer film and the charge sensitive layer film into 2×2 cm sizes;

[0107] (2) Leading out a silver wire on the thin film electrode layer;

[0108] (3) A triboelectric sensor can be made by bonding it to a thin film charge sensitive layer.

[0109] Performance Testing

[0110] like Figure 1 As shown in the figure, the photos and infrared camera images of the double network structure hydrogel of gelatin / polyvinyl alcohol at high temperature (left) and room temperature (right) show its significant state changes. Gelatin has a unique thermal phase change property. The random coil and triple helix non-covalent cross-linked structure of the gelatin molecules will depolymerize and aggregate under temperature changes. At high temperature, the triple helix structure of gelatin disintegrates into a single chain state of random coil, and the intermolecular interaction is weakened, making the system liquid. At the same time, polyvinyl alcohol dissolves at high temperature to form a uniform molecular distribution, and no significant physical cross-linking is formed, so it also remains in a liquid state. When the temperature is lowered, the triple helix structure of the gelatin molecule is partially restored to form a stable three-dimensional network. At the same time, the hydrogen bonds and physical cross-linking between polyvinyl alcohol and gelatin and water molecules are further enhanced to form a double network structure. The enhancement of this cross-linking effect causes the hydrogel to solidify into a gel state. In this way, the gelatin / polyvinyl alcohol double network structure hydrogel is liquid at high temperature and solidifies into a gel state at room temperature.

[0111] The non-covalent cross-linking density in gelatin has an important influence on the critical temperature of the solid-liquid phase transition of the hydrogel. As a reversible non-covalent cross-linking, ionic cross-linking increases the molecular weight in the gel and increases the cross-linking density in the gel matrix, thereby changing the critical temperature of the solid-liquid phase transition of the hydrogel. After the introduction of the functional ingredients sodium chloride, citric acid and sodium citrate, the storage modulus (G') and loss modulus (G") of the hydrogel continued to increase with the cooling process. The solid-liquid phase transition temperature (i.e. tanδ = G" / G') also increased from 36.15°C and 37.14°C to 38.15°C accordingly. According to Figure 2 From the tanδ calculated from the data in, it can be seen that the critical temperature change trend of the solid-liquid phase transition is consistent with the change trend of the crosslink density. Under normal circumstances, the skin temperature of the human body is between 33°C and 34°C. The adjusted hydrogel solid-liquid phase transition temperature reaches 38.15°C, which can meet the general human epidermal adhesion requirements, which provides the possibility for the application of hydrogels on the human epidermis.

[0112] In the binary solvent system formed by glycerol and water, the polyvinyl alcohol molecule contains hydroxyl (-OH), and the gelatin molecule contains hydroxyl (-OH), carboxyl (-COOH) and amino (-NH 2), these functional groups can form hydrogen bonds with hydrogen atoms in other substances to enhance the adhesion of hydrogels. In a binary mixture of polyvinyl alcohol and gelatin, cross-linking may occur between polyvinyl alcohol and gelatin molecules to form a network structure, which improves the adhesion of hydrogels to other substances through bridging. In addition, when polyvinyl alcohol or gelatin molecules are close to molecules of other substances, the electron clouds between them will produce temporary dipole moments. The weak van der Waals forces generated by the mutual influence of instantaneous dipole moments can also enhance the adsorption performance between polyvinyl alcohol and gelatin-based hydrogels and other substances. Figure 3 The photos of hydrogels pasted onto metals, glass, polymer products, paper and other materials can demonstrate their strong adhesion ability.

[0113] The hydrogel of the present application can be poured into molds of different shapes to quickly fill various microstructure spaces, and the shapes can be shaped and presented in corresponding shapes according to the size and shape of the molds. Figure 4 As shown, they all rely on their good fluidity and plasticity, and fast curing speed.

[0114] like Figure 5 As shown, after the prepared hydrogel solution is thinly applied to the skin surface and solidified, it can be observed that the film is highly transparent and has the ability to fill the unevenness of the skin surface and maintain the skin texture and details, and can achieve a high degree of conformal contact with the biological surface. The components added to the gelatin / polyvinyl alcohol-based double-network structure hydrogel designed in this application are all bio-friendly, have good compatibility with human skin and are mild, will not cause skin allergies or irritation, and will not cause redness or other adverse reactions after long-term application. Compared with common medical bandages, after being pasted on the arm surface for 7 days and then peeled off, the skin surface where the hydrogel was pasted did not have any redness or other marks, and there was no pain. On the contrary, the skin surface where the bandage was pasted was red after peeling and there was residual glue on the edge. This shows that the hydrogel has good biological properties and excellent peeling performance.

[0115] The hydrogel solution was coated with a laboratory coating machine into a film with a thickness of 400 μm, and the film was left to stand at room temperature and pressure for 14 days and its shape (e.g. Figure 6 It was found that the hydrogel film remained stable in terms of surface morphology, size, etc., maintaining its original morphology and structure.

[0116] Glycerol molecules contain multiple hydroxyl (-OH) functional groups, which enable them to form hydrogen bonds with water molecules. This hydrophilicity enables glycerol to attract and bind water molecules and adsorb them into the hydrogel, thereby increasing the hydration capacity of the hydrogel. The viscosity of glycerol can also form a protective film on the surface of the hydrogel to prevent the evaporation and loss of water. Figure 7During the 14-day water loss monitoring process, the hydrogel showed good stability, with a water loss rate of almost 0, which did not affect its application and expansion on the skin surface.

[0117] The gelatin / polyvinyl alcohol-based double network structure hydrogel was thinly coated on the inner surface of the adherend, and uniaxial stretching was achieved by a laboratory tensile machine, and the tension and displacement were recorded to quantify its adhesion ability (see Figure 8 Left). Figure 8 (Middle) Data show that the adhesion strength of gelatin / polyvinyl alcohol-based double network structure hydrogel to polyvinyl chloride, copper sheet, ethyl cellulose film, polyimide film, paper, pig skin and polydimethylsiloxane are 9.620, 111.593, 123.605, 174.631, 117.895, 24.524 and 9.529 kPa respectively. It can be seen that the hydrogel has good adhesion to common materials including polymer composites, metals and biological tissues, especially the adhesion strength to pig skin is as high as 24.524 kPa, which is equivalent to the commonly used medical bandages, but no residual glue will be left when peeled off. In addition, Figure 8 (Right) The hydrogel demonstrates excellent adhesion strength among different types of materials, including polyimide film, copper sheet, and pig skin surfaces, while maintaining robust and repeatable adhesion properties. After three cycles of testing, there was no significant loss in adhesion strength.

[0118] Fig. 9 (Left) shows the peeling force curves of gelatin / polyvinyl alcohol-based double network hydrogel on surfaces with sweat, sweat hair and smooth skin. The nearly consistent curve trend shows that the application of this hydrogel is not restricted under different skin surface conditions, showing potential in the field of human motion monitoring. To further study the tensile fracture properties of gelatin / polyvinyl alcohol-based double network hydrogel films and determine the effect of its thickness on the mechanical properties of the material, the hydrogel solution was made into films of different thicknesses (0.3, 0.4, 0.5, 0.6, 0.7 mm) using a coating machine, and the fracture tensile test was carried out. Fig. 9 The curve shown in (middle) shows that the displacement and fracture strength of films of different thicknesses are not linearly proportional. Considering the tensile properties and structural stability of the material, this study selected a 0.4 mm thick film for subsequent performance characterization and application. Subsequently, the 0.4 mm thick hydrogel film was subjected to 1000 cycles of 100% strain tensile testing. Fig. 9 The curve data (right) shows that after 100 cycles of stretching, the stretching performance has a certain hysteresis, but in the process of 100 to 1000 stretching, the stretching performance is stable. This result proves that the hydrogel material has excellent viscoelasticity.

[0119] In summary, mechanical property tests further proved that gelatin / polyvinyl alcohol-based double network structure hydrogel is a flexible material with excellent viscoelasticity and has broad application prospects, including skin patch biosensors, flexible electronic products, and smart medical devices.

[0120] Graphene is a single-layer carbon atom sheet with excellent electrical conductivity, thermal conductivity and surface area. It is one of the ideal materials for preparing high-performance electrodes in flexible wearable sensors. Polyethylene dioxythiophene-polystyrene sulfonate dispersion composites also have excellent conductivity, transparency and flexibility. Combining the two with gelatin / polyvinyl alcohol-based double network structure hydrogel, the two-dimensional structure of graphene and the high dispersion properties of polyethylene dioxythiophene-polystyrene sulfonate dispersion make the hydrogel electrode have a high specific surface area, which is conducive to the occurrence of electrochemical reactions and charge transfer. At the same time, it does not affect the high flexibility and plasticity of the hydrogel. It can be made into a flexible hydrogel electrode by leading it out with a silver wire. It can be attached to the surface of the skin on the chest to replace commercial electrodes for electrocardiogram monitoring (such as Fig.10 shown on the right). Fig.10 The middle right shows that the flexible electrode has controllable peeling properties. After being attached to the skin surface, the flexible electrode can be peeled off by blowing with a hair dryer. No additional peeling tools or chemicals are required during the peeling process, which is very easy to operate and convenient.

[0121] This application records the ECG signals of the homemade hydrogel electrode in two states, after exercise and at rest within 6 seconds, and the heart rate monitoring within 20 seconds. The curve results are as follows Fig.11 As shown, it is proved that the performance of the hydrogel electrode is comparable to that of commercial electrodes and is sufficient to replace them for widespread application.

[0122] In order to evaluate the long-term stability and electrical performance of the homemade hydrogel electrode, this application conducted a 14-day stability test on it. Fig.12The waveforms of electrical signals output by the homemade hydrogel electrodes during the measurement process are shown after the 0th day, the 7th day and the 14th day. It can be observed that compared with the standing state, the heart rate curve during walking within 4 seconds shows more periodic changes, and the output waveforms at these three time points are smooth and stable, without obvious signal attenuation or distortion. It can be seen that during the 14-day test period, the performance of the electrode remained stable, and there was no decline in electrical performance over time. After long-term use, it can still provide high-quality electrical signal transmission. This is mainly due to the hydrogel substrate with a double network structure of gelatin and polyvinyl alcohol, combined with polyethylene dioxythiophene-polystyrene sulfonate dispersion and graphene conductive material, which not only provides excellent mechanical properties and conductivity, but also gives the electrode excellent anti-drying and anti-degradation capabilities. In addition, the introduction of glycerol further enhances the water-locking effect of the hydrogel, preventing the electrode from dehydrating and degrading during long-term use.

[0123] In order to further verify the performance stability of the homemade hydrogel electrodes in different scenarios, this application conducted real-time monitoring experiments of ECG signals under various conditions. Fig.13 As shown in (left), the experiment was designed to monitor ECG signals in three electrode states: bending, squeezing, and stretching. The experimental results show that compared with commercial electrodes, the performance of the homemade hydrogel electrodes in these three states is still stable, with high consistency in waveform shape and amplitude, no obvious drift or noise, and clear amplitude and stable period.

[0124] The signal-to-noise ratio is an important indicator for measuring electrode performance and evaluating electrode signal acquisition capabilities. It reflects the ratio between the useful signal recorded by the electrode and the environmental noise. A higher signal-to-noise ratio means that the electrode can capture and retain biological signals more effectively, thereby improving the quality and reliability of the signal. A stable signal-to-noise ratio indicates that the electrode has consistent signal acquisition capabilities under different conditions (such as time, environment, etc.), which is particularly important for long-term monitoring and real-time applications. Fig.13 (Right) As shown, in the three states of bending, squeezing and stretching, the signal-to-noise ratio of the homemade hydrogel electrode is 32.788, 30.580 and 33.504 decibels respectively, which are significantly better than commercial electrodes. This shows that the designed flexible hydrogel electrode not only has good signal acquisition and transmission capabilities, but also can maintain stable performance under different mechanical deformation conditions. In summary, the homemade flexible hydrogel electrode shows good application prospects in ECG monitoring and biosensing applications. It can stably record cardiac electrical activity under different mechanical deformation conditions and has significant signal acquisition and transmission capabilities, which lays a solid foundation for its promotion in practical applications.

[0125] There are a large number of hydrogen bonds and cross-linked structures in both polyvinyl alcohol and gelatin molecules. Hydrogen bonds are a common type of non-covalent bond in hydrogels, with moderate strength and a certain degree of reversibility. When a hydrogel is damaged, the molecular chains at the damaged site may be partially broken or loosened, resulting in structural damage to the gel. However, when appropriate heat is applied, the molecular chains in the hydrogel begin to undergo thermal motion, and the hydrogen bonds can be rearranged and reformed under the action of thermal energy, thereby promoting self-repair of the damaged site. This rearrangement of hydrogen bonds enables the molecular chains at the damaged site to reconnect, restoring the integrity and functionality of the material, giving the hydrogel a unique ability to self-heal upon heating. Fig.14 As shown in the figure, the hydrogel electrode was artificially damaged, and the electrode film that was split into two was placed on a 50℃ heating table and heated for 30 seconds. During the heating process, it was observed that the hydrogel electrode at the split point healed back into one piece. The tensile test showed that the healed hydrogel electrode still maintained good toughness and could still withstand the weight of a 20g weight (see Fig.14 right), and did not separate again from the fracture.

[0126] Fig.15 The ECG monitoring capabilities of the hydrogel electrode were compared when intact, damaged, and healed. It was observed that the output curve waveform of the damaged electrode showed obvious abnormal fluctuations and could not work normally. In contrast, the output curve of the healed electrode was similar to that of the original electrode, showing stable and reliable working performance. In addition, the long-term monitoring results further verified that the performance of the healed film electrode has not weakened.

[0127] In recent years, flexible wearable smart devices with miniaturization and high integration have attracted more and more attention. Non-contact friction nanogenerator (triboelectric) sensors with high sensitivity, fast response speed and self-powered use the mechanical energy generated by friction to drive the movement of charges between nanomaterials, thereby realizing self-powered and non-contact energy conversion and data acquisition, and have broad application prospects in the fields of environmental monitoring and intelligent health monitoring. At present, there are two modes of non-contact triboelectric sensor structure design, namely double electrode and single electrode mode. In the former, there is a pair of friction electrodes with a certain distance gap in the sensor structure, and the generation of voltage signals depends on the relative movement of the two electrodes. The latter only needs one electrode in the device structure, and other materials that can undergo electrostatic induction serve as another electrode to realize the transfer of charges between each other. Compared with the former, the latter gets rid of the constraints of device size and expands the application range of the sensor to the indoor environment. This application further combines gelatin / polyvinyl alcohol-based double network structure hydrogel with triboelectric sensors, giving triboelectric sensors the characteristics of flexibility, and realizing the new development of flexible self-powered sensors.

[0128] Cobalt nanoporous carbon is a nitrogen-doped carbide based on a metal organic framework. Its high specific surface area is conducive to the adsorption of molecules and the catalytic reaction. Its rich pore structure facilitates the diffusion and transfer of molecules in it, and helps the carrier to which it is attached to obtain a strong electronegativity. A hydrogel with strong electrostatic induction ability can be obtained by uniformly mixing cobalt nanoporous carbon particles in a gelatin / polyvinyl alcohol-based double network structure hydrogel. A hydrogel made of it can be made into a thin film and combined with the aforementioned thin film electrode to produce a bio-friendly hydrogel-based flexible non-contact triboelectric sensor, such as Fig.16 The upper layer of the sensor is a charge-sensitive layer, and the lower layer is an electrode layer, which has good conductivity and collects the charge generated by the charge-sensitive layer under stimulation.

[0129] In order to obtain the best non-contact triboelectric performance, this application further explores the effects of the added content of cobalt nanoporous carbon and different positive electrode materials on the overall performance of the device. Under the condition of a fixed non-contact distance of 1 cm, ethyl cellulose is used as the positive charge sensing material, and a hydrogel-triboelectric sensor that easily generates negative charges is used to form a signal generator. The exciter drives the positive electrode material and the sensor to perform a "close-away" periodic motion at a constant non-contact vibration frequency of 5 Hz, and the sensor output voltage values ​​with gradient contents ranging from 1%, 1.5%, 2%, 2.5% to 3% are measured, such as Fig.17 As shown, they are approximately 0.275V, 0.49V, 0.496V, 0.64V and 0.264V respectively, showing a trend of first rising and then falling. It can be seen that the influence of the added content of the sensitive material on the performance of the sensor device is not positively correlated. The sensitive layer design of the sensor device finally adopts 2.5% cobalt nanoporous carbon. Under the same other conditions, different positive charge sensing materials are replaced, metal (aluminum sheet, copper foil), polymer (polyimide, ethyl cellulose, rubber), paper, and copper foil as the positive charge sensing material. The friction voltage output of the hydrogel-triboelectric sensor is large, up to 0.849V, and the device performance is the best. In subsequent experiments, copper foil will continue to be selected as the sensing object of the sensor to evaluate the performance of the device.

[0130] Fig.18 In a normal indoor environment (temperature 28°C, humidity 30%), ethyl cellulose film was used as the friction object, the non-contact distance was controlled to be 1 cm, the movement frequency was 5 Hz, and the surface area was 2×2 cm 2 The performance of the triboelectric sensor with an overall thickness of about 0.53 mm is stable at an output current density of 5 nA / cm 2 The transferred charge is about 0.5nC, the output waveform is smooth, and the sensor performance is stable.

[0131] Based on the coupling principle of triboelectricity and electrostatic induction, the hydrogel-triboelectric sensor can dynamically transfer charge between any positive electrode material. The hydrogel-triboelectric sensor is connected to the designed circuit and combined with the application program to convert the dynamic response of the sensor into a matching voltage signal output. Fig.19 In the laboratory, rubber gloves were used as the positive electrode material. During the "approach-contact-release-distance" action cycle, the sensor output voltage signal size was inversely proportional to the distance between the finger and the sensor. When the non-contact distance was the largest (2 cm), the sensor output relative voltage was 0.065V. During the gradual approach process, the output relative voltage gradually increased and reached a peak value at the moment of contact; during the distance process, the output relative voltage gradually decreased to 0. In this way, three action cycles were carried out, and the signal response law was consistent, and the curve fluctuation was stable.

[0132] The human body can also be used as a positive electrode material to transfer charges between the hydrogel-triboelectric sensor, expanding the application scenarios of triboelectric sensors to indoor environments for monitoring human motion status. Fig. 20 As shown in (left), the experimenter gradually backed away from the sensor at a distance of 0.8m and made an arm swinging motion. As the distance gradually increased, the peak-to-peak difference of the sensor output waveform gradually decreased. When the experimenter backed away to 4.0m, the sensor could still output a stable waveform curve. When the test distance increased further, the waveform became disordered and irregular, indicating that the maximum motion monitoring distance of the sensor is 4.0m. Compared with previously reported literature, the performance of this sensor has certain advantages.

[0133] Before the sensor is at a fixed distance, the difference in the amplitude of different movements determines the difference in the amount of transferred charge between the human body and the sensor, which enables the triboelectric sensor to identify and monitor human movement behavior. Fig. 20 (Right) shows that when the distance from the sensor is 0.8m, as the swing amplitude increases, the corresponding voltage signal becomes more obvious, and the maximum peak voltage difference can reach about 1V. The output waveform of jumping jacks changes relatively little, while the output waveform of jogging in place changes more frequently. The peak voltage difference of the high-five action can reach about 2V at most due to the simultaneous coordination of the arms and legs.

[0134] The purpose of artificial intelligence research is to expand human intelligence by exploring the essence of wisdom - to enable intelligent subjects to understand data, learn from it, and use knowledge to achieve specific goals and tasks, such as language recognition, image and text recognition, human-computer dialogue, expert systems, machine learning, robots and intelligent driving. Triboelectricity is a sensor that can achieve functional response without contact. If multiple sensors are combined and applied, the order of induction can make the signal output between sensors different in time, thereby realizing the application of trajectory recognition. Therefore, if Fig.21As shown, hydrogel-triboelectric sensors with consistent performance are organized into a 3×3 array, and the data of each sensor is collected through the module and uploaded to the computer application in real time. The difference in voltage signals is visualized by the algorithm, and the movement trajectory of the target object can be monitored. When the finger moves non-contact along the "L"-shaped trajectory at the corresponding position of the array, the corresponding sensor will immediately respond, generate voltage changes, and successively output the charge transfer as curve fluctuations, accurately identifying the "7-4-1-2-3" trajectory on the display. Similarly, the "Z" and "S" trajectories can also be accurately distinguished. This hydrogel-triboelectric sensor is expected to play a greater role in the fields of smart medical care, flexible electronic devices, and human-computer interaction in the future.

[0135] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a gelatin / polyvinyl alcohol-based double network structure hydrogel, characterized in that: The following steps are involved: A1. Dissolve sodium chloride, citric acid and sodium citrate in deionized water, then add glycerin, gelatin powder and polyvinyl alcohol powder, and soak for 2 to 3 hours; wherein the mass ratio of sodium chloride, citric acid, sodium citrate, deionized water, glycerin, gelatin and polyvinyl alcohol is 9.0-9.5:0.8-1.2:8-12:75-85:55-65:35-45:35-45; A2. The mixture obtained in step A1 is heated for 1 to 1.5 hours until completely dissolved, and the temperature is controlled in the range of 90 to 95°C; A3. The solution obtained in step A2 is stirred at a speed of 1000 to 1500 revolutions per minute for 2 to 2.5 hours until it is uniform to obtain a hydrogel solution; A4. Pour the hydrogel solution obtained in step A3 evenly onto a coating machine, apply it to a film of a certain thickness, and let it stand to cool and form to obtain a gelatin / polyvinyl alcohol-based double network structure hydrogel.

2. A gelatin / polyvinyl alcohol-based double network structure hydrogel prepared by the preparation method according to claim 1.

3. An application of the gelatin / polyvinyl alcohol-based double network structure hydrogel according to claim 2 in the preparation of a flexible hydrogel electrode or a charge sensitive layer of a hydrogel-triboelectric sensor or a hydrogel-triboelectric sensor.

4. A method for preparing a flexible hydrogel electrode, characterized in that: The following steps are involved: B1. Dissolve sodium chloride, citric acid and sodium citrate in deionized water, add polyethylene dioxythiophene-polystyrene sulfonate dispersion and graphene dispersion and stir evenly, then add glycerol, gelatin powder and polyvinyl alcohol powder and soak for 2 to 3 hours; wherein the mass ratio of sodium chloride, citric acid, sodium citrate, deionized water, glycerol, gelatin, polyvinyl alcohol, polyethylene dioxythiophene-polystyrene sulfonate dispersion and graphene dispersion is 9.0-9.5:0.8-1.2:8-12:75-85:55-65:35-45:35-45:75-85:155-165; B2. The mixture obtained in step B1 is heated for 1 to 1.5 hours until completely dissolved, and the temperature is controlled in the range of 90 to 95°C; B3. The solution obtained in step B2 is stirred at a speed of 1000 to 1500 revolutions per minute for 2 to 2.5 hours until it is uniform to obtain a hydrogel solution; B4. Pour the hydrogel solution obtained in step B3 evenly on a coater, apply it to obtain a film of a certain thickness, let it stand and cool to form a flexible hydrogel electrode.

5. A flexible hydrogel electrode prepared by the preparation method according to claim 4.

6. Use of the flexible hydrogel electrode according to claim 5 in preparing a hydrogel-triboelectric sensor.

7. A method for preparing a hydrogel-triboelectric sensor charge sensitive layer, characterized in that: The following steps are involved: C1. Dissolve sodium chloride, citric acid and sodium citrate in deionized water, then add cobalt nanoporous carbon, glycerol, gelatin powder and polyvinyl alcohol powder, and soak for 2 to 3 hours; wherein the mass ratio of sodium chloride, citric acid, sodium citrate, cobalt nanoporous carbon, deionized water, glycerol, gelatin and polyvinyl alcohol is 9.0-9.5:0.8-1.2:8-12:5-10:75-85:55-65:35-45:35-45; C2. The mixture obtained in step C1 is heated for 1 to 1.5 hours until completely dissolved, and the temperature is controlled in the range of 90 to 95°C; C3. The solution obtained in step C2 is stirred at a speed of 1000 to 1500 revolutions per minute for 2 to 2.5 hours until it is uniform to obtain a hydrogel solution; C4. Pour the hydrogel solution obtained in step C3 evenly on a coating machine, scrape and coat it to obtain a film of a certain thickness, let it stand and cool to form a hydrogel-triboelectric sensor charge sensitive layer.

8. A hydrogel-triboelectric sensor charge sensitive layer prepared by the preparation method according to claim 7.

9. Use of the charge sensitive layer of the hydrogel-triboelectric sensor according to claim 8 in the preparation of a hydrogel-triboelectric sensor.

10. A method for preparing a hydrogel-triboelectric sensor, characterized in that: The following steps are involved: D1. Cutting the flexible hydrogel electrode prepared according to claim 5 and the hydrogel-triboelectric sensor charge sensitive layer prepared according to claim 8; D2. Lead out a silver wire from the flexible hydrogel electrode; D3. Bond the flexible hydrogel electrode, silver wire and the charge sensitive layer of the hydrogel-triboelectric sensor to obtain the hydrogel-triboelectric sensor.

Citation Information

Cited By

  • Graphene composite hydrogel interface evaporation material as well as preparation method and application thereof

    CN121628265A